1981
DOI: 10.3758/bf03197559
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal processing in the auditory and visual modalities

Abstract: The authors would especiallylike to thank Bennet B.Murdock, Jr., for his encouragement. Eric Eich contributed many thoughtful comments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
1

Year Published

1984
1984
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 22 publications
(20 reference statements)
4
40
1
Order By: Relevance
“…Although some have disputed this claim (e.g., Handel, 1988), many have argued that the visual modality is better at processing spatial information, whereas the auditory modality is more sensitive to temporal information-a view that Glenberg and Swanson (1986) have termed the temporal distinctiveness theory. In support, Metcalfe, Glavanov, and Murdock (1981) reported that auditory stimuli are better recalled by temporal order but that visual stimuli are better recalled by spatial location. In the processing of pattern information, auditory rhythms are learned at a faster rate (Handel & Buffardi, 1968) and are better remembered (Glenberg & Jona, 1991;Glenberg, Mann, Altman, Forman, & Procise, 1989) than visual rhythms.…”
Section: Temporal Processing In the Auditory Versus Visual Modalitiessupporting
confidence: 66%
“…Although some have disputed this claim (e.g., Handel, 1988), many have argued that the visual modality is better at processing spatial information, whereas the auditory modality is more sensitive to temporal information-a view that Glenberg and Swanson (1986) have termed the temporal distinctiveness theory. In support, Metcalfe, Glavanov, and Murdock (1981) reported that auditory stimuli are better recalled by temporal order but that visual stimuli are better recalled by spatial location. In the processing of pattern information, auditory rhythms are learned at a faster rate (Handel & Buffardi, 1968) and are better remembered (Glenberg & Jona, 1991;Glenberg, Mann, Altman, Forman, & Procise, 1989) than visual rhythms.…”
Section: Temporal Processing In the Auditory Versus Visual Modalitiessupporting
confidence: 66%
“…Converging evidence for a temporal-distinctiveness theory of recency comes from a study that showed that temporal information is more faithfully represented given verbal rather than orthographic item presentations (Metcalfe, Glavanov, & Murdock, 1981). Although this study has been interpreted as showing that the auditory modality offers finer grain temporal encodings than the visual modality, it might be more prudent to conclude that the temporal characteristics of typical auditory stimuli are better represented in memory than are the temporal characteristics of typical visual stimuli.…”
Section: Discussionmentioning
confidence: 90%
“…There is good evidence that processing of temporal and spatial information is modality-specific, in the sense that temporal information is best processed through hearing and spatial information is best processed through vision. For example, the temporal order of a set of stimuli is better remembered when the stimuli are auditory and the spatial order is better remembered when the stimuli are visual (Metcalfe, Glavanov, & Murdock, 1981;O'Connor & Hermelin, 1978). A consequence of this modality specificity is that, as was suggested by Glenberg and Swanson (1988), recency differences between modalities may reflect a more fine-tuned encoding of temporal information for auditory presentation than for visual presentation.…”
mentioning
confidence: 79%